2002
DOI: 10.1016/s0304-405x(02)00228-3
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium and welfare in markets with financially constrained arbitrageurs

Abstract: We propose a multiperiod model in which competitive arbitrageurs exploit discrepancies between the prices of two identical risky assets traded in segmented markets. Arbitrageurs need to collateralize separately their positions in each asset, and this implies a financial constraint limiting positions as a function of wealth. In our model, arbitrage activity benefits all investors because arbitrageurs supply liquidity to the market. However, arbitrageurs might fail to take a socially optimal level of risk, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
617
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 988 publications
(661 citation statements)
references
References 24 publications
38
617
3
3
Order By: Relevance
“…Given our findings on bank capital and securities trading, our results are consistent with models of financial intermediation where the capital level of banks affects asset demand (Xiong, 2001;Gromb and Vayanos, 2002;Brunnermeier and Pedersen, 2009;Adrian and Shin, 2010;He and Krishnamurthy, 2013;Brunnermeier and Sannikov, 2014).…”
supporting
confidence: 85%
“…Given our findings on bank capital and securities trading, our results are consistent with models of financial intermediation where the capital level of banks affects asset demand (Xiong, 2001;Gromb and Vayanos, 2002;Brunnermeier and Pedersen, 2009;Adrian and Shin, 2010;He and Krishnamurthy, 2013;Brunnermeier and Sannikov, 2014).…”
supporting
confidence: 85%
“…Typically, skilled investors will seek to expand their profitable positions either through trading leverage (short positions funding long positions) or by soliciting outside capital from less skilled investors. However, in theoretical models such as Aiyagari and Gertler (1999), Gromb and Vayanos (2002), Geanakopolis (2003), Fostel and Geanakopolis (2008), Brunnermeier and Pedersen (2009) and Kondor (2009) leverage constraints can result in sudden reversals if idiosyncratic declines lower the value of collateral and force correlated liquidations. Fear of forced liquidations limit the leverage arbitrageurs are willing to employ and therefore the capital these arbitrageurs can devote to eliminating anomalies.…”
Section: Stock Price Momentum During Crsp and Victorian Eras: Abnormamentioning
confidence: 99%
“…There is a large body of theoretical literature exploring the effects of arbitrage capital on asset price dynamics based on two slightly different approaches (e.g., Xiong (2001), Kyle and Xiong (2001), Gromb and Vayanos (2002), Pedersen (2009), Kondor (2009), Krishnamurthy (2009), andDanielsson, Shin, andZigrand (2010)). These models commonly show that after arbitrageurs suffer large losses on their current positions, reduced risk appetite can cause them to liquidate positions despite the fact that the positions become even more profitable.…”
Section: Capital Constraintsmentioning
confidence: 99%
“…Kiyotaki and Moore (1997) developed a dynamic model to show that through their role as collateral for loans, durable assets (such as land) can amplify small, temporary shocks to technology or income distribution to generate large, persistent fluctuations in output and asset prices. Gromb and Vayanos (2002) showed that margin constraints can force arbitrageurs to prematurely liquidate arbitrage positions at losses and thus contribute to inefficiency in asset prices. Brunnermeier and Pedersen (2009) highlighted that margin constraints can be destabilizing and market liquidity and traders' funding liquidity can be mutually reinforcing, leading to liquidity spirals.…”
Section: Credit Cyclesmentioning
confidence: 99%